2015
DOI: 10.1109/jsen.2014.2384050
|View full text |Cite
|
Sign up to set email alerts
|

Electric-Field Assisted Desorption of Water Molecules in DNA Functionalized CNT Network

Abstract: This paper introduces the concept of electric field assisted desorption (EAD) of water molecules from the surface of DNA functionalized carbon nanotube (DFC) resistive network when a bias voltage V DS is applied across it. EAD at a given V DS is measured in terms of the characteristic life-time of desorption τ . The bias voltage produces an electric field E that aligns the molecular dipoles of water parallel to E. Mutually aligned neighboring dipole moments of water maximize the potential energy and drives the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…With increase in electric field E the dipoles increasingly align themselves in the direction of the field to form a polarized system of mutually interacting dipoles and thereby increasing the potential energy of the system. Desorption allows the dipoles to return to a state of lower potential energy [50].…”
Section: Plasma Catalysismentioning
confidence: 99%
“…With increase in electric field E the dipoles increasingly align themselves in the direction of the field to form a polarized system of mutually interacting dipoles and thereby increasing the potential energy of the system. Desorption allows the dipoles to return to a state of lower potential energy [50].…”
Section: Plasma Catalysismentioning
confidence: 99%
“…After IA-CNT channels were exposed to moisture, water molecules were absorbed on the surfaces of IA-CNTs. During this process, a charge-transfer incident took place because of the difference in the electrical potential between water molecules and IA-CNTs. , In turn, this showed that the electrical conductivity could change under the humid environment (Figure a). Furthermore, electrical conductivity variation could occur by the difference in induced charge transfer of various humid contents.…”
Section: Resultsmentioning
confidence: 99%